Information and analytical technologies for decision support in environmental monitoring systems of amalgamated territorial communities - Moshensky, Andriy; Savchenko, Igor (Technologies and Engineering, 2025)
The relevance of this study is conditioned by the increasing need to improve the effectiveness of environmental monitoring of amalgamated territorial communities in the context of growing anthropogenic and military impacts on the environment. The purpose of the study was to create an integrated decision support system for environmental monitoring, which allows combining data from different sources, continuously monitoring the state of ecosystems, predicting changes, and quickly responding to environmental threats. In the course of the research, a systematic approach, mathematical modelling of ecosystem dynamics, the least squares method for identifying model parameters based on limited data were applied, including cloud technologies, the Internet of Things, crowdsourcing platforms, and sensor networks for collecting and processing information were introduced. Data integration was carried out from government, public and departmental sources, which provided comprehensive coverage of various types of environmental impacts. The main results of the study were: development of a multi-level organisational structure of the monitoring system, construction of discrete and continuous mathematical models for assessing and predicting the state of ecosystems, implementation of recurrent algorithms for adapting models to changes in the environment. The system helped to ensure constant monitoring of industrial, agro-industrial and military-anthropogenic impacts, identify potential threats in a timely manner, assess their impact, and make informed management decisions to reduce environmental risks. The developed decision support system helps to effectively manage environmental risks, contributes to improving environmental safety and sustainable development of amalgamated territorial communities. The integration of advanced information technologies, mathematical models and public involvement in the monitoring process creates a new paradigm of environmental management in crisis conditions